Effect of Rosa damascena on the Severity of Depression and Anxiety in Postmenopausal Women: A Randomized, Double-blind, Placebo-controlled Clinical Trial - Qamar Riazi; Masoumeh Simbar; Sedigheh Amir Ali AKbari; Faraz Mojab; Nezhat Shakeri5 (Mashhad University of Medical Sciences, 2021)
Background: Depression and anxiety as the most common psychological disorders reduce the quality of life in women during menopause. Aim: Given the potential therapeutic properties of Rosa damascena, the present study aimed to investigate the effect of Rosa damascena on the severity of depression and anxiety in postmenopausal women. Method: This clinical trial was conducted on 110 postmenopausal women in Tehran, Iran, during 2020. The participants in the intervention group received 500 mg dried Rosa damascena capsules, and the control group received placebo capsules three times a day (once every 8 hours) for 40 days. The data were collected using a demographic characteristics form, Beck's Depression Inventory, Spielberger's State-Trait Anxiety Inventory, and adverse effects questionnaire. Subsequently, the data were analyzed in SPSS software (version 19) through the independent t-test, chi-square, Mann-Whitney, and repeated measures tests. Results: There was no difference in the mean score of depression before and 20 days after the intervention in the intervention group; however, this difference was significant 40 days after the intervention (p <0.05). The severity of anxiety differed significantly in the intervention group on days 20 and 40 post-intervention (p <0.001); however, these changes were not significant in the placebo group. The mean score of anxiety 20 and 40 days and depression 40 days after the intervention showed a significant difference between the two groups (p <0.001). Implications for Practice: It seems that R. damascena has effects on postmenopausal depression and anxiety. Accordingly, menopausal women are recommended to use R. damascena as an efficient non-pharmacological intervention.